Is innovation really a determinant of internationalisation? The case of Slovenian internationalised companies. (1st January 2014) - Ruzzier, Mitja; Hojnik, Jana; Lipnik, Aleš
Based on a sample of 108 Slovenian companies, from the 1, 000 most internationalised ones, we strived to explore the relationship between two strategic directions – innovation and internationalisation. The relationships between factor of innovation and the dependent variables of internationalisation (scale and scope) have been tested with regression analysis. The results have confirmed that models consisting of innovation and internationalisation scope (as a dependent variable) are statistically significant and can be supported, while models dealing with the relationship between the innovation factor and internationalisation scale as a dependent variable cannot be supported. Therefore, the results lead us to the conclusion that innovations are determinants of internationalisation scope of the Slovenian most internationalised companies, but do not determine the extent of their international activities.